(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Macrosiphine aphid Neotoxoptera violae (Pergande) is detected for the first time in Sicily (Italy) on common violet (Viola odorata L.), on wich, during a period of nearly two years, it performed several parthenogenetic generations (anholocycle ).